4-H Youth Development Programming in Underrepresented Communities - Shanon K. Junge; Vanessa Starr Spero; Niki Crawson; J. R. Davis; Tara Dorn; Beth Rasa Edwards; Stacy Hall; Karen Henry; Heather Janney; Beth Kerr; Andrea Lazzari; Abby Morgan; et al. (EDIS, 2023)
This is part of a series of guides that have been updated with permission from 4-H National Council. This resource guide is designed to be used by Extension professionals and after-school providers to deliver positive youth development programs in underrepresented areas or with underrepresented populations. It includes information on identifying underserved or underrepresented audiences and potential challenges to their participation in 4-H programming.